Factor analysis of enterprise resource planning applications at PT. Hanampi Sejahtera Kahuripan - Iskandar, Panca Pratama; Ratri Wahyuningtyas (International Journal of Financial, Accounting, and Management, 2024)
Purpose: This study aims to solve the problems of ERP technology acceptance in PT. Hanampi Sejahtera Kahuripan (PT.HSK) and help employees adapt to using new technology. Method: The contribution of this research is to consider the problem using a factor analysis method based on the TAM and TIB models. In this research, the author took a quantitative approach through a survey involving 137 PT. HSK employees. Results: After being analyzed using Confirmatory Factor Analysis (CFA), six factors were produced that influence the implementation of ERP information systems at PT. HSK. These factors are the Convenience Factor (factor 1), effectiveness factor (factor 2), behavior factor (factor 3), understanding factor (factor 4), performance factor (factor 5), and importance factor (factor 6). The research results show that six new factors were discovered, and the convenience factor emerged as the most influential in the acceptance of ERP technology at PT. HSK. Contribution: PT. HSK must pay attention to the convenience factor in the implementation and development of the ERP system so that employees can feel that using the ERP system can make their work faster and easier. Limitations: There are several limitations in this research, including the number of respondents and the research object that only focuses on PT. HSK, and the information provided by respondents through the questionnaires sometimes does not show their “true opinions.”